RGMa Participates in the Blood–Brain Barrier Dysfunction Through BMP/BMPR/YAP Signaling in Multiple Sclerosis - Zhang, Lei; Tang, Shi; Ma, Yue; Liu, Junhang; Monnier, Philippe; Li, Hang; Zhang, Rongrong; Yu, Gang; Zhang, Mengjie; Li, Yongmei; Feng, Jinzhou; Qin, Xinyue (Frontiers in Immunology, 2022)
Infiltration of inflammatory cells into central nervous system （CNS） through the dysfunctional blood-brain barrier (BBB) comprised a vital role and occurred in the early stage of MS. However, the mechanisms underlying BBB dysfunction are still poorly understood. Repulsive guidance molecule-a (RGMa) participant in the pathogenesis of multiple sclerosis (MS) but its role need to be further explored. This study aimed to evaluate whether RMGa regulates BBB permeability in endothelial cells and MS and to elucidate the mechanism may concerned. We induced experimental autoimmune encephalomyelitis (EAE) model in C57BL/6 mice and human brain microvascular endothelial cells (HBMECs) culture. BBB permeability are evaluated under different specifically intervention. Our results showed that RGMa is expressed in endothelial cell in HBMECs and EAE mice. RGMa and its signaling counterpart bone morphogenetic protein 2 (BMP2)/bone morphogenetic protein receptor type II (BMPRII) were gradually increased with the disease progression. Furthermore, downstream effector yes-associated protein (YAP) together with tight junctional proteins Zonula Occludens 1 (ZO-1) and claudin-5 was significantly declined with EAE progression and BBB disruption. Overexpression of RGMa in HBMECs by lentivirus induced a significant BBB breakdown by permeability assay whilst knockdown of RGMa significantly cement the integrity of BBB. Furthermore, specifically activating BMPR II or inhibiting YAP based on knockdown of RGMa results in a significant decrease of ZO-1 and claudin-5 in vitro. On the contrary, inhibitory of BMPR II or activation of YAP after upregulating RGMa abrogates the downregulation of ZO-1 and claudin-5 in HBMECs. In addition, serum soluble RGMa level (sRGMa) was higher expressed in MS patients, especially in MS patients with Gd+ lesions, which is consistent with the disruption of BBB. In conclusion, this study demonstrates that RGMa causes BBB dysfunction through BMP2/BMPR II/YAP in endothelial cells, thereby leading to the disruption of BBB integrity in MS. It could be a novel therapeutic target on BBB permeability in MS.